2016
DOI: 10.1186/s13068-016-0658-z
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and metaproteomic analyses of a corn stover-adapted microbial consortium EMSD5 reveal its taxonomic and enzymatic basis for degrading lignocellulose

Abstract: BackgroundMicrobial consortia represent promising candidates for aiding in the development of plant biomass conversion strategies for biofuel production. However, the interaction between different community members and the dynamics of enzyme complements during the lignocellulose deconstruction process remain poorly understood. We present here a comprehensive study on the community structure and enzyme systems of a lignocellulolytic microbial consortium EMSD5 during growth on corn stover, using metagenome seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 73 publications
(93 reference statements)
6
84
0
Order By: Relevance
“…However, MMs belonging to Acidobacteria , Firmicutes , and Proteobacteria were enriched in the NCC network (Figure b). Species of Firmicutes can degrade hemicellulose and cellulose by producing various enzymes (xylanases, β‐xylosidases, α‐glucuronidases, and acetyl xylan esterases; Zhu et al, ) and inhibit plant pathogens by producing antibiotics (surfactin, iturin, fengycin, etc. ; Qi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, MMs belonging to Acidobacteria , Firmicutes , and Proteobacteria were enriched in the NCC network (Figure b). Species of Firmicutes can degrade hemicellulose and cellulose by producing various enzymes (xylanases, β‐xylosidases, α‐glucuronidases, and acetyl xylan esterases; Zhu et al, ) and inhibit plant pathogens by producing antibiotics (surfactin, iturin, fengycin, etc. ; Qi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the bacterial phyla Proteobacteria , Firmicutes , and Bacteroidetes were found to be prevalent, and each was associated with a metabolic niche within the consortium. Due to greater assignment of (hemi)cellulolytic GHs to members of Firmicutes and Bacteroidetes , it was concluded that such bacteria act mainly on corn stover holocellulose, while Proteobacteria genes were primarily associated with lignin degradation . Similarly, an anaerobic biogas fermenter fed with agricultural wastes was also shown to be populated by Firmicutes and Bacteroidetes , with the former predominating .…”
Section: Omics Approaches For the Screening Of Lignocellulolytic Micrmentioning
confidence: 99%
“…Yang et al [45] reported a degree of synergy of 1.35 for the hydrolysis of delignified corn stover when studying the synergistic effect between a commercial enzyme preparation and a bifunctional enzyme consisting of an acetyl xylan esterase and a α-l-arabinofuranosidase. For glucan conversion of delignified corn stover, Zhu et al [46] found a synergy of 1.96 between a hemicellulase preparation EMSD5 (including xylanases, β-xylosidases, α-l-arabinofuranosidases, α-glucuronidases, and acetyl xylan esterases) and the commercial cellulase from T. reesei. These findings revealed the significant role of glycosidases for efficient lignocellulose degradation.…”
Section: Discussionmentioning
confidence: 99%
“…These findings revealed the significant role of glycosidases for efficient lignocellulose degradation. Moreover, 9 carbohydrate binding modules (CBMs) were also observed, which could help hydrolyze substrate more effectively [46]. In T. harzianum EM0925 enzyme enzyme cocktail, a LPMO with abundance of 3.23% was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation